1984
DOI: 10.1016/0005-2736(84)90013-0
|View full text |Cite
|
Sign up to set email alerts
|

Sterol-phospholipid interactions in model membranes Effect of polar group substitutions in the cholesterol side-chain at C20 and C22

Abstract: The interactions of phospholipids with four different cholesterol derivatives substituted with one OH or one keto group at position C2o or C22 of the side-chain were studied. The derivatives were the 22,R-hydroxy; 22,S-hydroxy; 22-keto-and 20,S-hydroxycholesterol. Two aspects of the interactions were investigated: (1) the effect of the cholesterol derivatives on the gel--, liquid crystalline phase transition of dipalmitoylphosphatidylcholine (DPPC) and of dielaidoyiphosphatidylethanolamine (DEPE) monitored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…This contrasts with 22,S-OHCH or 20,S-OHCH, which appear to orient vertically at large molecular areas (39). In our work, the slight rises in surface pressures between 140 and 200 Å 2 /molecule from 0.7 and 1.2 mN/m to 1.1 and 2.2 mN/m for 27OHCH and 25OHCH, respectively, compared to the sharp rise with 22,R-OHCH (39), are consistent with the entire side chain of these terminally hydroxylated sterols lying horizontal at the interface. In this configuration, the side chain will undergo cis-trans conformational isomerizations and alter its length.…”
Section: Monolayers Of Pure Cholesterol and Its Substituted Analoguesmentioning
confidence: 71%
See 2 more Smart Citations
“…This contrasts with 22,S-OHCH or 20,S-OHCH, which appear to orient vertically at large molecular areas (39). In our work, the slight rises in surface pressures between 140 and 200 Å 2 /molecule from 0.7 and 1.2 mN/m to 1.1 and 2.2 mN/m for 27OHCH and 25OHCH, respectively, compared to the sharp rise with 22,R-OHCH (39), are consistent with the entire side chain of these terminally hydroxylated sterols lying horizontal at the interface. In this configuration, the side chain will undergo cis-trans conformational isomerizations and alter its length.…”
Section: Monolayers Of Pure Cholesterol and Its Substituted Analoguesmentioning
confidence: 71%
“…5) suggests that like the dihydroxy bile acids (21), 25OHCH and 27OHCH are oriented horizontally at the interface at large molecular areas (Ͼ140 Å 2 ), with the 3-OH and the side chain OH anchored to the interface. Also based on surface balance experiments, the horizontal orientation of 22,R-OHCH, another side chain OHCH, has been suggested, because of a lift-off at 103 Å 2 /molecule (39). This contrasts with 22,S-OHCH or 20,S-OHCH, which appear to orient vertically at large molecular areas (39).…”
Section: Monolayers Of Pure Cholesterol and Its Substituted Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence anisotropy, differential scanning calorimetry, and 31P NMR demonstrated that oxidized derivatives of cholesterol did not suppress the melting phase transition of phospholipid liposomes as did pure cholesterol (Vincent & Gallay, 1983;Gallay et al, 1984). Oxidized sterols did not bind to the same site on oxysterol carrier protein as cholesterol (Kandutsch & Shown, 1981).…”
Section: Discussionmentioning
confidence: 96%
“…By analyzing the structure of ginsenoside Rg3, we found that its steroid ring structure, side chain of C17, and hydroxyl of C3 site satisfy all conditions proposed by researchers that required for liposome membrane regulators (fig. S1) ( 19 ), which means that Rg3 has the potential as a stabilizer by inserting into the liposome membrane and interacting with phospholipids. The glucose moieties in the hydrophilic part of Rg3 will theoretically extend out of the liposome surface, which is the perfect ligand for glucose transporter 1 (Glut1) overexpressed in TNBC ( 20 ), implying that Rg3 may have the ability to target and capture CTCs after inserted into liposomes.…”
Section: Introductionmentioning
confidence: 99%